A 9-Point Risk Assessment for Patients Who Inject Drugs and Require Intravenous Antibiotics: Focusing Inpatient Resources on Patients at Greatest Risk of Ongoing Drug Use. (25th August 2018) - Eaton, Ellen F; Mathews, Ronnie E; Lane, Peter S; Paddock, Cayce S; Rodriguez, Jorge Martin; Taylor, Benjamin B; Saag, Michael S; Kilgore, Meredith L; Lee, Rachael A
Abstract: A 9-point risk assessment identified persons with a history of injection drug use who were safe for discharge. "Low-risk" patients were discharged with outpatient antibiotics; others continued inpatient treatment. Use of the assessment reduced the mean length of stay by 20 days and total direct cost by 33%, creating capacity for an additional 333 patients.